"Grab gatorade!": food marketing, regulation and the young consumer. (12th November 2018) - Elliott, Charlene
Abstract : Purpose: This paper aims to examine current regulatory initiatives on food marketing to young people and to highlight unique considerations when it comes to teenagers. Design/methodology/approach: This paper integrates the policy and public health literature with the literature on childhood studies and consumer studies. Findings: Since the policy goal is to mitigate the impact of food marketing on young people's attitudes and behaviours, it is necessary to recognize the consumer competencies of teenagers and consider the social and symbolic meanings of food for them. It is suggested that radical media literacy, coupled with food literacy, is essential to navigating a complex food environment filled with promotional messages for ultra-processed foods. Research limitations/implications: This analysis has implications for policy development. Practical implications: Consideration of age – in terms of different developmental competencies, motivating factors and additional initiatives to support healthy eating (such as teaching media literacy skills) – is necessary to policy development related to food marketing to children. Originality/value: Little research integrates the literature on food policy/regulation with the critical work on consumer studies/childhood studies. This commentary also directs attention to novel areas of consideration related to teenagers and food marketing.